Design and logistical considerations for the randomized adaptive non-inferiority storage-duration-ranging CHIlled Platelet Study. (February 2023) - Zantek, Nicole D; Steiner, Marie E; VanBuren, John M; Lewis, Roger J; Berry, Nicholas S; Viele, Kert; Krachey, Elizabeth; Dean, J Michael; Nelson, Stacy; Spinella, Philip C
Background: Platelet transfusion is a potentially life-saving therapy for actively bleeding patients, ranging from those undergoing planned surgical procedures to those suffering unexpected traumatic injuries. Platelets are currently stored at room temperature (20°C–24°C) with a maximum storage duration of 7 days after donation. The CHIlled Platelet Study trial will compare the efficacy and safety of standard room temperature–stored platelets with platelets that are cold-stored (1°C–6°C), that is, chilled, with a maximum of storage up to 21 days in adult and pediatric patients undergoing complex cardiac surgical procedures. Methods/Results: CHIlled Platelet Study will use a Bayesian adaptive design to identify the range of cold storage durations for platelets that are non-inferior to standard room temperature–stored platelets. If cold-stored platelets are non-inferior at durations greater than 7 days, a gated superiority analysis will identify durations for which cold-stored platelets may be superior to standard platelets. We present example simulations of the CHIlled Platelet Study design and discuss unique challenges in trial implementation. The CHIlled Platelet Study trial has been funded and will be implemented in approximately 20 clinical centers. Early randomization to enable procurement of cold-stored platelets with different storage durations will be required, as well as a platelet tracking system to eliminate platelet wastage and maximize trial efficiency and economy. Discussion: The CHIlled Platelet Study trial will determine whether cold-stored platelets are non-inferior to platelets stored at room temperature, and if so, will determine the maximum duration (up to 21 days) of storage that maintains non-inferiority. Trial registration: ClinicalTrials.gov, NCT04834414